Optimization and ZSPORE Analysis of Affinity Purification Coupled with Tandem Mass Spectrometry in Mammalian Cells - Shitao Li; Martin E. Dorf (Journal of Proteomics and Genomics Research, 2012)
Defining protein-protein interactions is essential for understanding the mechanisms by which cells regulate basic functions, such as metabolism, transcription, and signal transduction. Affinity purification followed by tandem mass spectrometry (AP-MS) has application for discovery of new interactors regulating various cellular processes. Here we optimize the purification method for AP-MS and develop a simplified unbiased analytical tool, Z-score plus prey occurrence and reproducibility (ZSPORE) for data analysis. Using this pipeline we achieve a higher efficiency of AP-MS and enhanced identification of high confidence interacting proteins (HCIP) in mammalian cells. When applied to analysis of the innate immune interactome, these methods enhanced HCIP identification. In addition, we investigated the GRB2 complex, which is associated with signal transduction and cell growth. Twenty-four known GRB2 interacting proteins were identified plus 26 new GRB2 binding partners. Thus, these straightforward methods recapitulate known protein interactions, discover novel complexes, and allow mapping of protein interaction networks.
Keywords: protocol for affinity purification